“The Curious Impertinent” and The Second Maiden’s Tragedy: (Self)Subversive Discourses on Gender and Power - Serrano González, Raquel (2019)
This paper provides a comparative analysis of “The Curious Impertinent”, an interpolated novel in Don Quixote (1605), and The Second Maiden’s Tragedy, a play attributed to Thomas Middleton premiered in 1611. Cervantes’s story about the stratagem contrived by a jealous husband who persuades his closest friend to test his wife’s fidelity and the pernicious consequences that ensue is rewritten in the subplot of Middleton’s work and adapted to the Jacobean political and ideological context. The play’s main storyline also mirrors the Cervantine-inspired episode: the female protagonist is equally tempted by a tyrant, but, as opposed to the seduced wife, she resists stoically and gives up her life to prevent an otherwise unavoidable rape. Critics of both works are divided as to whether they uphold the dominant construction of women as ‘naturally’ inferior to men, both being permeated by a blatantly misogynistic language that perpetuates the ‘weaker vessels’ ideology. The analysis developed in this paper aims to prove that, even though each text was produced in a different social context –and hence has different political motivations–, both are self-subversive, as they undermine the dominant ideology of femininity and the consequent power hierarchy, in both the private and the public spheres.